The Soybean-Specific Maturity Gene E1 Family of Floral Repressors Controls Night-Break Responses through Down-Regulation of FLOWERING LOCUS T Orthologs - Xu, Meilan (Plant Physiol, 2015)
Photoperiodism is a rhythmic change of sensitivity to light, which helps plants to adjust flowering time according to seasonal changes in daylength and to adapt to growing conditions at various latitudes. To reveal the molecular basis of photoperiodism in soybean (Glycine max), a facultative short-day plant, we analyzed the transcriptional profiles of the maturity gene E1 family and two FLOWERING LOCUS T (FT) orthologs (FT2a and FT5a). E1, a repressor for FT2a and FT5a, and its two homologs, E1-like-a (E1La) and E1Lb, exhibited two peaks of expression in long days. Using two different approaches (experiments with transition between light and dark phases and night-break experiments), we revealed that the E1 family genes were expressed only during light periods and that their induction after dawn in long days required a period of light before dusk the previous day. In the cultivar Toyomusume, which lacks the E1 gene, virus-induced silencing of E1La and E1Lb up-regulated the expression of FT2a and FT5a and led to early flowering. Therefore, E1, E1La, and E1Lb function similarly in flowering. Regulation of E1 and E1L expression by light was under the control of E3 and E4, which encode phytochrome A proteins. Our data suggest that phytochrome A-mediated transcriptional induction of E1 and its homologs by light plays a critical role in photoperiodic induction of flowering in soybean.